On Archimedes' statics - Bacelar Valente, Mario (THEORIA. An International Journal for Theory, History and Foundations of Science, 2020)
Archimedes' statics is considered as an example of ancient Greek applied mathematics; it is even seen as the beginning of mechanics. Wilbur Knorr made the case regarding this work, as other works by him or other mathematicians from ancient Greece, that it lacks references to the physical phenomena it is supposed to address. According to Knorr, this is understandable if we consider the propositions of the treatise in terms of purely mathematical elaborations suggested by quantitative aspects of the phenomena. In this paper, we challenge Knorr's view, and address propositions of Archimedes' statics in their relation to physical phenomena.